Core cross-linked double hydrophilic block copolymer micelles based on multiple hydrogen-bonding interactions. Issue 20 (3rd April 2017) - Chen, Jingsi; Yan, Bin; Wang, Xiaogang; Huang, Qingxue; Thundat, Thomas; Zeng, Hongbo
Abstract : Facile preparation and characterization of core cross-linked micelles via strong multiple hydrogen bonds using well-defined thermo-responsive double hydrophilic block copolymers. Abstract : A facile route for the preparation of core cross-linked polymeric micelles via self-complementary multiple hydrogen bonds was developed. Double hydrophilic block copolymers of poly(ethylene glycol)- b -poly( N -isopropylacrylamide) (PEG- b -PNIPAm), with 2-ureido-4[1 H ]-pyrimidinone (UPy) functionality throughout PNIPAm block, were synthesized via reversible addition–fragmentation chain transfer polymerization. It was found that the strong dimerization of the self-complementary quadruple hydrogen-bonding UPy groups could induce non-covalent intermolecular bonding between the copolymer chains and serve as core cross-linking of the formed micelles. The stability and thermo-responsive properties of the obtained micelles with varying UPy side-group content were investigated by dynamic light scattering, atomic force microscopy and fluorescence spectroscopy. The PNIPAm core of the cross-linked micelles exhibits reversible thermo-responsive swelling/shrinking behavior, as evident from the hydrodynamic diameter changes detected during cyclic heating-cooling tests. The thermo-responsive loading and release of pyrene molecules (as a model hydrophobic drug) demonstrate a potential application of the synthesized core cross-linked micelles in controlled drug delivery. The results indicate that multiple hydrogen-bonding interactions between UPy moieties can be maintained in a hydrophilic aqueous environment, which provides a convenient approach to stabilize the micellar structures and maintain responsive behaviors of double hydrophilic block copolymers by core cross-linking. This work provides new insights into designing stable and stimuli-responsive polymer micelles with a wide range of applications in drug delivery, diagnosis and sensing.